RANCANG BANGUN APLIKASI IKHTIBAR TASHNIFI BERBASIS WEB UNTUK MAHASISWA BARU JURUSAN SASTRA ARAB - Ahsanuddin, Mohammad (Arabi : Journal of Arabic Studies, 2016)
In every academic year, the department of Arabic literature, Malang State University arranges ikhtibar tashnifi (placement test) for new students aimed to know their competence in Arabic language. Previously, the test was held through paper-pencil test. This research was aimed to develop steps in designing ikhtibar tashnifi web-based application for placement test and describe the use of web-based placement test. The method used was R&D (Research & Development). Some steps were conducted: preliminary study, product development, professional testing, revision, limited experiment, revision, and final product. The respondents were all the new students of Arabic literature department at the university academic year 2013. The research found the major concern in designing this application was observing, doing library research, and designing the program. Before it is used, the program should be first installed in the local server, creating database, and running the program. The validity of ikhtibar is 81,25%, while the result of media professional analysis is 85%.DOI: 10.24865/ajas.v1i2.7